Ensaios sobre deslocamentos pendulares: uma análise para a região metropolitana do Recife - Brito, Danyella Juliana Martins de (2014)
This thesis aims to evaluate the characteristics of urban mobility in the Metropolitan Region of Recife (RMR), identifying the strength of the commute flows and the role of migration experience over the urban mobility taking account a set of socioeconomic characteristics. To this purpose, we used a gravity model to analyze the main determinants of commuting among the cities in RMR. Moreover, we estimated the treatment effect of the past migration over the likelihood of a household head become a commuter. The following points summarize our main finds. First, the distance between the municipalities of residence and work/study decreases the commuting flows, i.e. the commuting flows are on average higher among nearest regions. Second, the index of local development (IDH) in the municipality of residence is negatively correlated with the commuting flows, while the most developed municipalities have attracted more commuters. Third, the migration experience is positively related to commuting flows, i.e., a household head who had migrated in the last decade increases his probability of become a commuter around 13.4 p.p.. Therefore, the results suggest that public policies directed to urban mobility should be designed taking account different levels of local development and migrations streams.